2010
DOI: 10.1155/2010/708481
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia for Emergency Caesarean Section in a Patient with Large Anterior Mediastinal Tumour Presenting as Intrathoracic Airway Compression and Superior Vena Cava Obstruction

Abstract: Anterior mediastinal mass is an uncommon pathology that presents significant anaesthetic challenges because of cardiopulmonary compromise. We present a case that presented in the third trimester of pregnancy with severe breathlessness, orthopnoea, and symptoms of superior vena cava obstruction. The patient had emergency Caesarean section under epidural anaesthesia with a good outcome. The paper discusses the relevant perioperative considerations for this complex scenario and reviews reports of similar conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…The study found that the incidence of cancer diagnosed either before or during pregnancy at their institution was 0.1%. This finding is consistent with the prevalence previously reported by a major anesthesia text [2] and quoted in other publications [4,5]. Of note, Tharmaratnam and Balki also found no difference in the frequency of malignancy diagnoses made before pregnancy as compared with during pregnancy.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The study found that the incidence of cancer diagnosed either before or during pregnancy at their institution was 0.1%. This finding is consistent with the prevalence previously reported by a major anesthesia text [2] and quoted in other publications [4,5]. Of note, Tharmaratnam and Balki also found no difference in the frequency of malignancy diagnoses made before pregnancy as compared with during pregnancy.…”
supporting
confidence: 92%
“…Although this case report provided no description of the patient's anesthetic care, the value of multidisciplinary patient management was emphasized in the article. Chiang et al [5] reported on a 34 year old woman at 34 weeks' gestation who was admitted with respiratory distress. A chest radiograph and computed tomography scan of the thorax showed an anterior mediastinal mass with extension into the left hemithorax and compression of the airway, heart, and superior vena cava.…”
mentioning
confidence: 99%
“…Initial diagnosis of a mediastinal mass in pregnancy is difficult to establish due to similarities of presenting signs and symptoms that mimic normal pregnancy [7], as well as the desire to avoid unnecessary radiographic imaging during pregnancy [8]. Anterior mediastinal masses compete with underlying vital structures including the heart, major vessels and airways, and can lead to obstruction of these airways, as well as main pulmonary arteries, atria, and superior vena cava.…”
Section: Discussionmentioning
confidence: 99%
“…We have included 136 reports, both full publications and abstracts, covering 158 cases (see also Supporting Information, Appendices S1–S6) . Case reports largely fall into two groups: those describing equipment, or a technique, for provision of general anaesthesia; or those identifying a woman who had predicted airway difficulty, who was managed with regional analgesia or anaesthesia with the aim of avoiding of general anaesthesia.…”
Section: Resultsmentioning
confidence: 99%